Avaliação imuno-histoquímica das galectinas-1, -3, -4 e -7 em carcinoma epidermóide de língua. - Alves, Pollianna Muniz (2009)
Several studies are carried out with aim to establish parameters to determine biologic behavior of oral squamous cell carcinoma, in order this neoplasm presents high rates of morbidity and mortality. The purpose of present research was to performe a clinic, morphologic and immunohistochemical analysis by the expression of galectins 1, 3, 4 and 7 in 65 cases of tongue squamous cell carcinoma, correlating this expression with clinics (outcome of the disease, metastasis and clinical staging) and morphologic parameters (malignancy histologic gradation system). The clinical and morphologic parameters analysed and expression of galectins 1, 3, 4 and 7 were submitted to statistical analysis (Qui2 test), observing that can be utilized as indicators of the biological behavior of the tongue squamous cell carcinoma. The galectin 1 was expressed in 87,7% of cases studied and it exhibit statistically significant correlation with metastasis (p=0,033) and clinical staging (p=0,016), it is located mostly in the citoplasm of the stomal cells. The immunoexpression of galectin 3 in 87,7% of cases was correlated with the presence of metastasis (p=0,033) and malignancy histological gradation system (p=0,031), observed, mostly of cases, in tongue squamous cell carcinoma of malignancy high grading. The galectin 4 showed no statistical significance to any of the parameters evaluated. The expression of galectin 7 in 73,8% of cases showed statistically significant correlation with the malignancy histologic grading (p=0,005), which is marking exclusively found in neoplastic epithelial cells, in the mostly of cases, it is found in cytoplasm and membrane (50%). The expressive immunopositivy of the galectins 1, 3 and 7, observed in this research, leads us to suggest a broad participation of these proteins in oral carcinogenesis, and its possible use as markers of biological behavior and tumor progression in cases of squamous cell carcinoma of the tongue